Recent review on Synthesis, spectral Studies, versatile applications of azo dyes and its metal complexes - Roohinaz Khanum; R.A. Shoukat Ali; H.R. Rangaswamy; S.R. Santhosh Kumar; A.G. Prashantha; A.S. Jagadisha (Results in Chemistry, 2023)
The review paper strives to concentrate on the categorization and diverse synthesis techniques of azo dyes and their complexes over the past ten years. Azo dyes are frequently included as the primary scaffold in many of organic compounds with its emerging commercial and biological properties. Present review article also covers several techniques for identifying and validating azo dyes along with their metal complexes, including all spectral techniques like UV, infrared, NMR, mass spectrometry etc., with auxiliary methods, such as X-ray diffraction TGA-DTA (thermal gravimetric analysis and differential thermal analysis), SEM AND TEM (scanning electron microscopy and tunnelling electron microscopy) methods, and ESR are used to investigate the nature of the azo dyes. The current review also discusses numerous uses for azo dyes and its complexes under the heading colorant, as well as non-colorant uses in a variety of industries and bio medical uses.